Investigation of the nonlinear behaviour in real exchange rates in developing regions. Issue 5 (12th March 2018) - Karlsson, Hyunjoo Kim; Månsson, Kristofer; Sjölander, Pär
ABSTRACT: This article examines whether the purchasing power parity (PPP) theory holds or not for the economies in different developing regions located in Africa, Asia and Latin America. In order to investigate this issue, a nonlinear panel unit root test is used to determine if some or all of the real exchange rates in a panel follow a stationary exponential smooth transition autoregressive process. By applying the nonlinear panel unit root test, our results demonstrate an empirical support for the theory of PPP for the economies in developing regions.